Characterization of hard-segment crystalline phase of thermoplastic polyurethane in the presence of butane and glycerol monosterate and its impact on mechanical property and microcellular morphology. (10th March 2017) - Hossieny, N.; Shaayegan, V.; Ameli, A.; Saniei, M.; Park, C.B.
Abstract: The effects of glycerol monosterate (GMS) and high-pressure butane on the phase-separation and crystallization of the hard segment (HS) of thermoplastic polyurethane (TPU) were investigated. Small and wide angle x-ray diffraction, polarized optical microscopy and atomic force microscopy were used to characterize the crystalline morphology of TPU under various conditions. Overall, 60% higher HS crystallinity was observed in TPU-GMS samples annealed with butane compared to the neat-TPU samples. The toughness and Young Modulus in the TPU-GMS samples were increased due to the higher HS crystallinity compared to the neat-TPU samples. The HS crystallites were effectively utilized as heterogeneous bubble nucleation sites to induce microcellular morphologies in the TPU microstructure. Compared to neat-TPU, the TPU-GMS microcellular morphology showed higher cell density over the wide saturation temperature of 150–170 °C due to the increased HS phase separation and crystallization mechanism in the presence of GMS and dissolved butane. Graphical abstract: Highlights: Hard segment (HS) crystallized faster in TPU with presence of GMS. Plasticizing butane significantly induced a large number of HS crystals in TPU. HS crystallization reduced activation energy for bubble nucleation in TPU microstructure. Microcellular TPU foams was achieved with butane due to HS crystallization.